Comparing Maternal and Paternal Parenting in Student Academic Performance: A Systematic Literature Review From 2013 To 2023 - Zhao, Yang Yang; Ghani, Faizal Bin A; Hoque, Kazi Enamul (International Research-Based Education Journal, 2025)
Students’ academic success is significantly associated with parents. Given the varied effects of parenting on student academic performance, it is a strong need for independent research on the impact of maternal parenting and paternal parenting to learn more about the mechanisms of parenting influence. By systematically reviewing the literature from 2013 to 2023, this study aims to provide the landscape of maternal parenting and paternal parenting as well as to compare the effect of them on student academic performance. The results revealed insufficient published studies in the field and uneven research in terms of geographic distribution, the volume of studies, and the stage of student learning. The analysis found that the effects of maternal and paternal parenting were both controversial. Regarding the manners, involvement level, time spending, and the effect size, the influence of maternal parenting and paternal parenting on student academic performance were distinguished significantly. These findings are not only helpful to reveal the mechanism of maternal and paternal parenting differences on student academic performance, but also provide practical guidance for schools and parents